2020
DOI: 10.1371/journal.pone.0230868
|View full text |Cite
|
Sign up to set email alerts
|

Two coastal Pacific evergreens, Arbutus menziesii, Pursh. and Quercus agrifolia, Née show little water stress during California's exceptional drought

Abstract: California's coastal climate is characterized by rainy winters followed by a dry summer season that is supplemented by frequent fog. While rising temperatures and drought caused massive tree mortality in central California during the 2011-2015 extreme drought, dying trees were less common in the central coast region. We hypothesized that cooler, maritimeameliorated temperatures reduced the effects of drought stress on coastal vegetation. To test this, weekly measurements of water potential and stomatal conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…For example, resilience and persistence in the face of drought, does not always equal exceptional embolism resistance, as our field data have shown. There are many unexpected ways in which plants can survive or avoid massive droughts (Jacobsen et al ., 2007; Holmlund et al ., 2016, 2019, 2020; Chacon et al ., 2020), and there may be others. Characterising and understanding variation in species vulnerability to cavitation, xylem architecture, xylem anatomy, phenology and other factors will continue to enrich our understanding of how plants have evolved to manage the most acute stress they face on land.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, resilience and persistence in the face of drought, does not always equal exceptional embolism resistance, as our field data have shown. There are many unexpected ways in which plants can survive or avoid massive droughts (Jacobsen et al ., 2007; Holmlund et al ., 2016, 2019, 2020; Chacon et al ., 2020), and there may be others. Characterising and understanding variation in species vulnerability to cavitation, xylem architecture, xylem anatomy, phenology and other factors will continue to enrich our understanding of how plants have evolved to manage the most acute stress they face on land.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have used the centrifuge method to generate vulnerability‐to‐cavitation curves (VCs) on fern petioles (Pittermann et al ., 2011; Burns et al ., 2016; Holmlund et al ., 2016), in which the petioles were spun at progressively higher speeds corresponding with more negative water potentials. With this and other hydraulic methods such as air injection (Sperry & Saliendra, 1994) or bench drying (Jacobsen & Pratt, 2012; Martin‐StPaul et al ., 2014; Chacon et al ., 2020), segments are removed from the instrument after reaching a desired water potential, and the per cent loss of conductivity (PLC) is determined as (1 − K h /K MAX ) × 100, where K h is the segment hydraulic conductivity (K) standardised for length at a given water potential, and K MAX is the maximum hydraulic conductivity at which all xylem conduits are water filled (Sperry et al ., 1988). While air injection pushes air into the xylem rather than pull it in as in the centrifuge method, both approaches should, in theory, yield very similar results.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been suggested that the centrifuge method does not overestimate vulnerability to embolism in stem segments with cut‐open vessels (Jacobsen & Pratt, 2012; Sperry et al ., 2012; Tobin et al ., 2012; Hacke et al ., 2014), and that there is no accidental formation of gas‐filled vessels in xylem segments that are cut in water whilst under negative pressure (no cutting artefact observed in Venturas et al ., 2015, 2019; Nardini et al ., 2017). These alternative viewpoints suggest that exponential vulnerability curves may be valid (Sperry et al ., 2012), and consequently support previous reports of high levels of native embolism (up to 60–90%) in functional sapwood, even under mild drought (Pockman & Sperry, 2000; Domec et al ., 2006; Jacobsen et al ., 2007; Chacon et al ., 2020; Percolla et al ., 2021). This discrepancy in xylem vulnerability continues to cause confusion about the frequency of drought‐induced embolism events in planta .…”
Section: What Is Known About Drought‐induced Embolism Formation?mentioning
confidence: 99%
“…UC Santa Cruz data have already been used in a number of comparative analyses (e.g., [27,45,60,[69][70][71][72][73][74][75][76][77]), and the availability of the complete data sets should allow for more widespread use. Equally importantly, we demonstrate that the development of the FERP, as an integral part of experiential learning in forest ecology for hundreds of novice student scientists and as an accessible platform for undergraduate and graduate research (e.g., [78][79][80][81]), is supportive of generating highquality ecological data of value to the broad research community. E120_N240, E160_N040, E160_N120, E160_N240, and E160_N280; values from across the stations were averaged to represent climate patterns within the FERP (Figure A2).…”
Section: Discussionmentioning
confidence: 82%